Clonal Planting Stock for Development of Agroforestry in India —A Historical Perspective - lal, Piare (Indian Farming, 2015)
Genetically superior clonal planting stock of field tested clones of eucalyptus, poplar and other species can be used in Agroforestry for getting improved quality of timber and pulp wood. True to type clonal planting stock has also ensured substantial improvement in quality of the timber and pulpwood produced from other tree species.